AB0105 Inhibition of A Streptococcal Cell Wall Model of Arthritis Flare by Repository Corticotropin Injection. (15th July 2016) - Higgins, P.; Decker, D.; Becker, P.
Abstract : Background: Repository corticotropin injection (RCI), a melanocortin peptide preparation, is FDA approved as adjunctive therapy for short term administration to tide patients over acute episodes or exacerbations of rheumatoid arthritis (RA), but has not been studied in an animal model of arthritis flare. Objectives: To test the efficacy of RCI in a Streptococcal cell wall-induced model of arthritis flare in rats [1]. Methods: Dark Agouti rats were primed on day 0 by an intra-articular injection of a proteoglycan/polysaccharide (PGPS) preparation from Streptococcal cell wall into the right ankle and vehicle (phosphate buffered saline) into the left. On days 14 and 28, transient arthritic flares were induced in the ankle by intravenous injection of PGPS. Caliper measurements of the right and left paw diameters were made daily beginning on the day of induction of the first flare. RCI was administered subcutaneously at doses of 40, 160, and 400 U/kg beginning day 1 after induction of the first flare and dosed every other day until animals were sacrificed on day 35, after recovery from the second flare. Arthritis was assessed by measuring the diameter difference between the right (PGPS injected) and left ankles. Histologic analysis was performed on the paws obtained at sacrifice (day 35). Results: RCI dose-dependently inhibited paw swelling in rats after induction of both the first and second arthritic flares. Doses of 160 U/kg and 400 U/kg inhibited physical signs of the first flare by 69% (p<0.01) and 86% (p<0.001) and inhibited the second flare by 87% (p<0.0001) and 90% (p<0.0001), respectively. Histologic analysis showed that inflammatory cell infiltration into joints was significantly decreased by 53% (p<0.01) and 77% (p<0.0001) at the 160 and 400 U/kg doses of RCI, respectively, and that total histopathologic damage scores, which included measures of pannus, cartilage damage, bone resorption and periosteal bone formation were significantly reduced by 78% and 91% at 160 and 400 U/kg, respectively. Conclusions: These preclinical results demonstrate the efficacy of RCI in an animal model of RA flare and support the potential clinical benefit of the drug for the treatment of inflammatory arthritis exacerbations. References: Schopf L, Anderson K, Jaffee B. Rat models of arthritis: Similarities, differences, advantages, and disadvantages in the identification of novel therapeutics. In: C Stevenson, L Marshall, D Morgan (eds): In Vivo Models of Inflammation. 2006 Birkhauser Verlag, Basel. 1–34. Disclosure of Interest: P. Higgins Employee of: Mallinckrodt, D. Decker Employee of: Mallinckrodt, P. Becker Employee of: Mallinckrodt